Efetividade e segurança do inspirômetro de incentivo para prevenção em complicações pulmonares pós-operatórias em cirurgia abdominal alta: revisão sistemática e metanálise - Guimarães, Michele Marchese Fagundes [UNIFESP] (2010)
Background: Upper abdominal surgical procedures are associated with a high risk of postoperative pulmonary complications. The risk and severity of postoperative pulmonary complications can be reduced by the judicious use of therapeutic maneuvers that increase lung volume. Our objective was to assess the effect of incentive spirometry (IS) compared with no therapy or physiotherapy including coughing and deep breathing, on all-cause postoperative pulmonary complications, and mortality in adult patients admitted for upper abdominal surgery. Objectives: To assess the effects of IS compared with no such therapy (or other therapy) on allcause postoperative pulmonary complications (atelectasis and acute respiratory inadequacy) and mortality in adult patients admitted for upper abdominal surgery. Search strategy: We searched the Cochrane Central Register of Controlled Trials (CENTRAL) (The Cochrane Library 2006, Issue 3), MEDLINE, EMBASE, and LILACS (from inception to July 2006). There were no language restrictions. Selection criteria: We included randomized controlled trials of IS in adult patients admitted for any type of upper abdominal surgery, including patients undergoing laparoscopic procedures. Data collection and analysis: Two authors independently assessed trial quality and extracted data. Main results: We included 11 studies with a total of 1754 participants. Many trials were of only moderate methodological quality and did not report on compliance with the prescribed therapy. Data from only 1160 patients could be included in the meta-analysis. Three trials (120 patients) compared the effects of IS with no respiratory treatment. Two trials (194 patients) compared IS with deep breathing exercises. Two trials (946 patients) compared IS with other chest physiotherapy. None showed evidence of a statistically significant effect of IS. There was no evidence that IS is effective in the prevention of pulmonary complications. Authors’ conclusions: We found no evidence regarding the effectiveness of the use of IS for prevention of postoperative pulmonary complications in upper abdominal surgery. This review underlines the urgent need to conduct well-designed trials in this field. There is a case for large randomized trials of high methodological rigor in order to define any benefit from the use of IS regarding mortality.